Embodied Language Comprehension Requires an Enactivist Paradigm of Cognition - Van Elk, Michiel; Slors, Marc; Bekkering, Harold (Frontiers in Psychology, 2010)
Two recurrent concerns in discussions on an embodied view of cognition are the ‘necessity question’ (i.e. is activation in modality-specific brain areas necessary for language comprehension?) and the ‘simulation constraint’ (i.e. how do we understand language for which we lack the relevant experiences?). In the present paper we argue that the criticisms encountered by the embodied approach hinge on a cognitivist interpretation of embodiment. We argue that the data relating sensorimotor activation to language comprehension can best be interpreted as supporting a non-representationalist, enactivist model of language comprehension, according to which language comprehension can be described as procedural knowledge—knowledge how, not knowledge that—that enables us to interact with others in a shared physical world. The enactivist view implies that the activation of modality-specific brain areas during language processing reflects the employment of sensorimotor skills and that language comprehension is a context-bound phenomenon. Importantly, an enactivist view provides an embodied approach of language, while avoiding the problems encountered by a cognitivist interpretation of embodiment.